Pulmonary alveolar proteinosis: time to shift?. (June 2015) - Papiris, Spyros A.; Tsirigotis, Panagiotis; Kolilekas, Likurgos; Papadaki, Georgia; Papaioannou, Andriana I; Triantafillidou, Christina; Papaporfyriou, Anastasia; Karakatsani, Anna; Kagouridis, Konstantinos; Griese, Matthias; Manali, Effrosyni D
Abstract : Pulmonary alveolar proteinosis (PAP) is categorized into hereditary, secondary and autoimmune PAP (aPAP) types. The common pathogenesis is the ability of the alveolar macrophages to catabolize phagocytized surfactant is affected. Hereditary PAP is caused by mutations involving the GM-CSF signaling, particularly in genes for the GM-CSF receptor and sometimes by GATA2 mutations. Secondary PAP occurs in hematologic malignancies, other hematologic disorders, miscellaneous malignancies, fume and dust inhalation, drugs, autoimmune disorders and immunodeficiencies. aPAP is related to the production of GM-CSF autoantibodies. PAP is characterized morphologically by the inappropriate and progressive 'occupation' of the alveolar spaces by an excessive amount of unprocessed surfactant, limiting gas exchange and gradually exhausting the respiratory reserve. Myeloid cells' immunity deteriorates, increasing the risk of infections. Treatment of PAP is based on its etiology. In aPAP, recent therapeutic advances might shift the treatment option from the whole lung lavage procedure under general anesthesia to the inhalation of GM-CSF 'as needed'.